From catalysts to bioactive organometallics: Do grubbs catalysts trigger biological effects? - Oehninger, Luciano; Alborzinia, Hamed; Ludewig, Stephanie; Baumann, Knut; Wölfl, Stefan; Ott, Ingo (ChemMedChem, 2011)
Grubbs up! Grubbs-type catalysts have potential as inhibitors of tumor-relevant enzymes, exhibit antiproliferative effects in cultured tumor cells, and influence cell metabolism. While the potencies of these catalysts are poor to moderate from a drug development prospective, their biological activity suggests that incorporating aspects of their structures could be beneficial for drug design.